Design and Development of a Car Rental Reservation Information System at CV. Alvin Jaya Mandiri - Ika Yusnita Sari; Imam Adlin Sinaga; Elvika Rahmi; Khairunnisa Khairunnisa (Jurnal Armada Informatika, 2026)
This study aims to develop a web-based car rental information system at CV. Alvin Jaya Mandiri to replace inefficient manual processes. The software development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, and documentation studies. The system enables online reservations, real-time vehicle availability monitoring, transaction management, and automated financial and inventory reports. It also provides a user-friendly interface for both administrators and customers. The results show that the system improves operational efficiency, data accuracy, and service quality, supporting digital transformation in the increasingly competitive car rental industry